2014
DOI: 10.1111/cfs.12163
|View full text |Cite
|
Sign up to set email alerts
|

Contact visits between foster children and their birth family: the views of foster children, foster parents and social workers

Abstract: It has been argued that contact visits between foster children and birth parents can help maintain attachment bonds and support the child's development. However, some research suggests that such visits can be detrimental. This study analyses the characteristics of contact visits and examines children's perceptions of the emotional relationship they have with foster carers and their biological parents. Participants were 104 non‐kinship foster children and their respective foster carers and social workers. Fifty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 14 publications
1
24
0
5
Order By: Relevance
“…Indigenous Elder) in the discussions between foster parents and resource workers. There was considerable overlap between responses in this concept and the literature indicating that ability to find some common ground (Holland and Gorey 2004) and move forward following a disagreement (Salas Martínez et al 2014) was favored as a quality of good relationships from both the perspectives of foster parents in the literature and workers in the present study. There was also attention in the literature to the need for openness to cultural differences and responsive practice that was sensitive to those differences (Mindell et al 2003).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Indigenous Elder) in the discussions between foster parents and resource workers. There was considerable overlap between responses in this concept and the literature indicating that ability to find some common ground (Holland and Gorey 2004) and move forward following a disagreement (Salas Martínez et al 2014) was favored as a quality of good relationships from both the perspectives of foster parents in the literature and workers in the present study. There was also attention in the literature to the need for openness to cultural differences and responsive practice that was sensitive to those differences (Mindell et al 2003).…”
Section: Discussionmentioning
confidence: 71%
“…This is aided by some advance strength in the relationship with agreement on some important issues (Holland and Gorey 2004) as well as a value of the other person (Mapp 2002) and ability to bridge differences of opinion as needed (Salas Martínez et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In several cases, this is due to Child Protection Services' beliefs that visits could be contrary to the child's well-being. In fact, some biological families that are allowed to have contact do not show up at arranged visits established by the Child Protection Services (Del Valle et al, 2008;Jimé nez & Palacios 2009;Salas et al, 2016).…”
Section: Contact Definitionmentioning
confidence: 99%
“…Because of the complexities and consequences, contact in foster care, specially visits, have been the subject of discussion and the topic of research in diverse contexts. The current study aims to present and explore the main outcomes on contact obtained in research projects developed in Portugal (Delgado, Carvalho, & Pinto, 2017) and Spain (Salas et al, 2016). The option of comparing different systems, bearing in mind the country's explicit socio-cultural characteristics and policies, aims at targeting what is unique in each country and what can be similar, independently of country context, in order to take advantage of the learning potential that diversity can provide.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that children and adults can have different perspectives on issues and emphasize other aspects of these issues. For example, foster parents evaluate birth parent contacts more negatively than children (Salas Martínez, Fuentes, Bernedo, & García-Martín, 2016). Moreover, youth emphasize autonomy in mental health support while foster parents are more concerned with reducing risk behavior (Stanley, 2007), and children's experiences do not always align with the professionally kept case records, for example regarding permanency and maltreatment histories (Cho & Jackson, 2016;Rolock & Pérez, 2016).…”
mentioning
confidence: 99%